Perceptions of urban poor with B40 status on the impact of the implementation of Movement Control Order (MCO) by employment sector: A case study at Kota Kinabalu city, Sabah - Adi Jafar; Fionna Geogre; Mohammad Tahir Mapa; Nordin Sakke; Ramli Dollah (Curtin Business School, 2021)
Communities with low incomes are vulnerable when facing dangerous situations. The Novel Coronavirus or Covid-19 is one of the examples of natural hazards that have spread around the globe, including Malaysia. Following the rapid spread of Covid-19 around the world, Malaysia has taken precautionary measures by implementing the Movement Control Order (MCO). The aim was to curb the transmission of Covid-19 in the country. However, the implementation of MCO has changed the daily routine of the community in general, particularly the low-income community. Therefore, this study aims to identify the impact of MCO implementation from the aspects of health and social relationship among the B40 group in Kota Kinabalu city, Sabah. Apart from that, this study also aims to identify the variable relationship of the B40 group’s category of employment sectors with agreement towards the MCO implementation. This study utilised questionnaire survey methods to obtain data in the field. Questionnaire data were analysed using the Principal Component Analysis (PCA) Technique, Crpss Tabulation Analysis, and Chi Square Test. The study found that the implementation of MCO brings positive benefits from the aspect of safety, health, and social relations among B40 group. The analysis also found that the majority of the respondents who work as civil servants are satisfied with the MCO implementation compared with respondents who are self-employed or business traders.